Nutritional anaemia in children in post supplementation era: A cross sectional study - Kumar, Rajesh; Singh, Manoj Kumar; Singh, Vineet Kumar; Kumar, Pankaj; Singh, Sheo Pratap; Agrwal, Renu; Dr, Chandrakanta (Asian Journal of Medical Sciences, 2021)
Background: Nutritional anemia is still the primary cause of anemia despite of various nutritional programmes in developing countries. Aims and Objective: The present study was planned to asses Iron, Folate, and Vitamin B12 deficiency anaemia in developing countries. Materials and Methods: This cross-sectional study was conducted at a tertiary care centre in Agra in collaboration with Institute of Genomics and Integrative Biology, New Delhi. Admitted children of age 6 months to 14 years having signs and symptoms of anaemia were included in the study. Sample size calculated was 157. All the cases were subjected to CBC, GBP, serum iron, ferritin, folate and vitamin B12 level estimation. Results: Out of 672 children, 157 children with clinical feature of anaemia were enrolled in the study. Among these 157 children, 52.87% were male. Percent proportion of anaemia was highest among toddlers (27.39%) and lowest in adolescent (10.83%). The maximum cases were of urban area (65.6%) and middle socioeconomic status (47.13%). Most of the children were undernourished/underweight (60.4%). Mean iron level was significantly low in female children, children of rural areas, low socioeconomic status and malnutrition/underweight. Mixed iron, folate and B12 deficiency was found in 48.41%, 30.57% and 22.93% cases respectively. In 24.20% cases no deficiencies were found and were classified as anaemia due to some unspecified causes. Conclusion: Nutritional deficiency anaemia is contributing to a large proportion of anaemic patients. More intensified programmes are needed especially for female children, children of rural areas, low socioeconomic status and malnutrition/underweight.